Origem e distribuição do plexo lombossacral de javali (Sus scrofa - Linnaeus, 1758) - Santos, Lázaro Antonio dos (2016)
It aimed to study the origin and distribution of the lumbosacral plexus of Sus scrofa. 30 specimens were used, with 13 females and 17 males, after being fixed in an aqueous 10% formaldehyde. Boars have five or six lumbar vertebrae and four sacral vertebrae. The lumbosacral plexus originates from the spinal cord segments from L2 to S4. The lateral femoral cutaneous nerve from L2 to L4 branches off to the psoas major and minor muscles, internal oblique of the abdomen, sub-iliac lymph nodes and the knee joint region skin. The femoral nerve L3 to L6 supplies the major psoas muscle, iliac minor psoas, femoral quadriceps, pectineus, emits saphenous nerve that innervates the sartorius muscle and fascia and skin of the knee and tarsus joints. The obturator nerve from L3 to L6 is distributed to the external obturator muscles, pectineus, gracilis and adductor. The gluteal cranial nerve from L4 to S1 innervates the gluteus medius and piriformis muscles. The gluteal caudal nerve from L6 to S2 emits branches to the superficial gluteal muscle. The sciatic nerve from L4 to S2 innervates the tensor muscles of the fascia lata, gluteus medius, deep gluteus, gluteus accessory, twins, femoral square, semitendinosus, semimembranosus, biceps femoris. The tibial nerve supplies the gastrocnemius, soleus, popliteal and the deep finger flexors in the plantar region that is divided into medial and lateral plantar nerves which branch off into digital plantar. The common fibular nerve is divided into superficial nerves and deep fibular. The deep fibular nerve emits branches to the cranial tibial, third fibular, long extensor of fingers, peroneus longus, lateral extensor digitorum and interosseous muscles. The superficial fibular nerve supplies the fascia joint of the tarsos, which continues as dorsal digital nerves. The pudendal nerve from S2 to S4 is distributed to muscles, external anal sphincter, levator ani, constrictor of the vulva, ischiocavernosus and bulbospongiosus, emits the dorsal branches of the clitoris and of the breast, that innervate the clitoris and skin of the vulvar region, respectively. The dorsal branch of the penis is distributed in the glans penis, prepuce and scrotum. The rectal caudal nerve from S2 to S4 is distributed to the levator ani, coccyx and external anal sphincter. The formation of the lumbosacral plexus, as well as sources and distributions of the nerves that form it, are similar to those described in the literature alluding to domestic animals.